Conceiving the old regime pronatalism and the politics of reproduction in early modern France - Tuttle, Leslie, 1967- (Oxford University Press, 2010)
The French obsession with population has roots in the old regime, when the French state used its power to convince French men and women to marry and procreate large families. Drawing on archival research, Tuttle explores the interactions of men women, and officials all vying for control of the reproductive process.